λ-MnO2 Thin Films with Sponge-Like Structures: Synthesis, Characterization and Physiochemical Applications - Khalid Abdelazez Mohamed Ahmed (Indonesian Journal of Chemistry, 2021)
Manganese dioxide has acquired significant research attentiveness in many fields over the past years because of its exciting physicochemical features. The magnetized λ-MnO2 thin films with sponge-like structures (TSLs) were prepared by hydrothermal-soft chemical and delithiation-lithium manganese process. The XRD, XPS, EDX, FESEM, TEM, HR-TEM, and N2 adsorption-desorption techniques were used to characterize the as-prepared product’s structure composition, morphology, and surface area. The particle growth details of λ-MnO2 are postulated by the oxidation-ionic change-delithiation (OID) mechanism. The electrochemical property was analyzed by galvanostatic discharge-charging, electrochemical impedance spectrum (EIS), and cyclic voltammetry (CV). Special attention of λ-MnO2 S.L.s is given to their applications in the degradation of methyl orange (MO) from wastewater under O2 air bubble pump and cathodic substance in the lithium-ion battery. Due to the peculiarity crystal form and morphology face, the λ-MnO2 TSLs might be promisingly applied in the various physicochemical area.